First Contacts of the Danubian Slavs and Avars: The Evidences from the Byzantine Writers and Archaeology - Kazanski, Michel (Antičnaâ drevnostʹ i srednie veka, 2023)
This article addresses the question of the archaeological sites relating to the Danube Slavs (Sclavi), who first came into contact with the Avars in the sixth century. The isolated groups of the people of the Prague culture penetrated into the area in between of the Danube and the Adriatic, Pannonia to the south-west of Lake Balaton and the Eastern Alps in particular, from the first third of the sixth century onwards. These settlements possess some features similar to the Slavic sites of the Prague culture. No doubts, this area ap- peared under the rule of the Avars when the Pannonian Lombards migrated to Italy in 568 AD and left their lands for the Avars. The cemetery of Regensburg-Grossprüfening in Bavaria is of particular importance for the correct understanding of the situation in the region under study. The site contained 22 Slavic cremation graves, where Merovingian goods appeared. There were a few graves featuring prestigious artefacts. It has been assumed that there was the resettlement of the Slavs, most likely being an elite military grouping, ca 568 AD, under the pressure of the Avar expansion. If this interpretation is correct, there was a departure of the elites of the Middle Danubian Slavs from the Avar power zone. Perhaps it resulted in a change of the social structure of the Pannonian Slavs, which explained their more dependent place in the Avar Khanate, in contrast to those of the Lower Danubian and Balkan Slavs, who also found themselves in the sphere of the Avar power.